2011
DOI: 10.1007/s00404-011-2195-0
|View full text |Cite
|
Sign up to set email alerts
|

Women’s well-being after Manchester procedure for pelvic reconstruction with uterine preservation: a follow-up study

Abstract: The modified Manchester procedure including reconstructive surgery for women with cervix elongation, with or without POP, prevented recurrent uterine prolapse and was well received in terms of patient's satisfaction, quality of life, and sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In a review comparing uterine preservation with hysterectomy, Kapoor et al [19] cautioned that the risk of cancer is the most significant disadvantage [20]. Studies comparing vaginal hysterectomy with uterine-sparing prolapse surgery have not demonstrated significant differences in objective or subjective cure rates, and there is no recognized standard procedure to suspend the uterus [14,16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…In a review comparing uterine preservation with hysterectomy, Kapoor et al [19] cautioned that the risk of cancer is the most significant disadvantage [20]. Studies comparing vaginal hysterectomy with uterine-sparing prolapse surgery have not demonstrated significant differences in objective or subjective cure rates, and there is no recognized standard procedure to suspend the uterus [14,16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a recent study, cervical length measured using the POP-Q system was more related to anatomical cervical length than that reported in an imaging study 12. Moreover, measuring D point in the POP-Q system was necessary to differentiate between true cervical elongation and uterine descent 131415…”
Section: Discussionmentioning
confidence: 92%
“…The uterosacral-Mackenrodt remnants are reattached to the cervical stump to strengthen it with the help of a Sturmdorff suture. In a longitudinal study, it was concluded that reconstructive surgeries for women with cervical elongation, with or without associated POP, was well received in terms of patient's satisfaction, improved quality of life and sexual function [3] . In a 3-year follow-up in Penang Hospital, Malaysia, the anatomical recurrence rate following vaginal hysterectomy was 4-7%, whereas recurrence was very rare after the Manchester procedure [4] .…”
Section: Discussionmentioning
confidence: 99%